Рукопис Матвія Десятого 1507 року: до визначення руської редакції церковнослов’янської мови - Наєнко, Галина (Slavia Orientalis, 2026)
The manuscript of Matthew the Tenth (1507) is an Old Church Slavonic record which despite the interest of many scholars has yet to be adequately researched. The author discusses features of the Rus´ian recension of Church Slavonic viewed through the prism of the multilingualism within the Grand Duchy of Lithuania. The Church Slavonic basis of the text under consideration is influenced by the South Slavic orthography as promoted by Patriarch Euthymius of Tarnovo: the amanuensis uses new graphs, punctuation symbols and diacritics, as well as changes ѧ>ѣ, ꙗ>а etc. The influence of prosta mova is demonstrated at both the Ukrainian and Belarusian language levels, especially in the realm of orthography, including instances of specific spelling. All this is likely to show the amanuensis’s dependency on the Rus´ian dialects (the new ѣ, the coalescence of i and y, the confusion of ѣ and ї, the dispalatalization of hushing (post-dental) consonants).